Penggunaan Benford’s Law dalam Menemukan Red Flag: Potensi Fraud pada Pengeluaran Pemerintah Daerah - Annisa, Nabila Qurota; Bakri, Muhammad Rafi (Direktorat Sistem Perbendaharaan, 2025)
Auditors frequently recognize transactions in financial statements that are suspected of having the potential to facilitate fraud. This study seeks to examine all indicators of red flags in the implementation of Indonesian regional government expenditures, including Personnel Expenditures (51), Goods & Services Expenditures (52), and Capital Expenditures (53). This study analyzes 22,329 transaction records from a regional government in 2023, subsequently evaluated by Benford's Law. The test results indicate that transactions nearing a specific threshold exhibit a higher likelihood of being fraudulent compared to others. Moreover, there exists a risk of fraud in transactions characterized by low nominal values yet high frequency of occurrence. Auditors may utilize these red flags as a basis for additional examination.